Surrogate-based optimization approach for capacitated hub location problem with uncertainty. Issue 1 (31st December 2023) - Kim, Junghyun; Chung, Changyun
Abstract: CJ Logistics has started to consider opening single new hub facility to expand the current transportation network system. This naturally leads to formulating a research question "where should the new hub facility be located in South Korea to minimize total transportation cost of the network system operated by the company?". This research aims to answer the question by proposing a surrogate-based optimization approach. In addition to finding an optimal location of the new hub facility, this research performs sensitivity analysis to study the correlation between hub capacity (i.e., the source of uncertainty) and transportation cost. The results indicate that (1) total transportation cost after the establishment of the new hub facility at the optimal location is reduced by approximately 14% compared to the current transportation network system and (2) the currently operated hub facility located in Daejeon has the greatest influence on total transportation cost; while the existing hub facilities located in Cheongwon, Yongin, and Gunpo have little impact on total transportation cost after the construction of the new hub facility. It is expected that the outcome of this research helps the company systematically manage the transportation network system when the new hub facility is constructed.